Kekerasan di Lingkungan Kampus: Tantangan dan Solusinya - nada, FITHROTUN (Maliki Interdisciplinary Journal, 2025)
Campus violence has become a significant issue affecting students, lecturers, and other staff. This violence includes physical, verbal, psychological, and sexual harassment, often underreported due to social stigma and weak reporting mechanisms. This article aims to explore the definition, types of violence, causes, impacts, and strategic steps to address violence within campus environments.Through literature review, it is found that campus violence is often triggered by seniority culture, lack of character education, academic social pressure, and weak regulations. Its impacts are multidimensional, including psychological trauma, decreased academic motivation, social isolation, and the financial burden of mental health rehabilitation. To address this issue, a comprehensive approach is needed, including the establishment of strict policies, integrating character education into curricula, providing psychological support services, conducting anti-violence campaigns, and collaborating with external organizations. These measures aim to create a safe and conducive campus environment that fosters intellectual, social, and emotional development for all academic community members.